Preventing Foodborne Illness Associated with Clostridium perfringens - Keith R. Schneider; Renée M. Goodrich-Schneider; Michael A. Hubbard; Dirk M. Sampath (EDIS)
Revised! FSHN03-5, a 3-page fact sheet by Keith R. Schneider, Renée Goodrich-Schneider, Michael A. Hubbard, and Dirk M. Sampath, provides food handlers, processors, and retailers information about foodborne illnesses caused by this Gram-positive bacterial pathogen that thrives in improperly stored meat and meat-products. Includes references. Published by the UF Department of Food Science and Human Nutrition, April 2010.